Propose new design for OSIM Health Center Level 2 Lot 2-38, Berjaya Times Square Sdn Bhd No 1, Jalan Imbi, 55100, Kuala Lumpur / Mohd Syarhan Nizam Abdul Ghani - Abdul Ghani, Mohd Syarhan Nizam (Faculty of Architecture, Planning and Surveying, 2004)
In today’s lifestyle, stress can aware you down. A healthy body and sound mind are vital assets in preventing illness. At OSIM, they like to share with the world their philosophy on the key of good health that is Relation, Spirit, Healthy living and Beauty. By focusing on Hygiene, Nutrition, and Fitness, OSIM use ail their knowledge’s about science, therapy, acupuncture and technology producing their product that make easy to take care of health and also take less time compare to traditional way. Although there is many competitor outside, OSIM have proven that they is the best by winning many award in International. By the mission to Bringing Healthy Lifestyle to People and the Vision to Be the Global Leader in Healthy Lifestyle Products, they have produced many useful products and still produce more with the experiment and research by the expert. With the company philosophy that is Challenging Your Spirit to Do Your Best, they try to break their business by giving new services and up grade their services by adding treatment and counseling in their business. In order to make this real; the OSIM Health Centre to introduce their product and feel the effect of the product In order to make sure this project success; survey, interview, research and fit back have been done to make sure that it not only give benefit to company but also to people, nation and world.